Complete mitochondrial genome and phylogenetic analysis of Ixodes persulcatus (taiga tick). Issue 1 (1st January 2017) - Sui, Shuo; Yang, Yu; Fang, Zhiqiang; Wang, Jiancheng; Wang, Jing; Fu, Yingqun; Hou, Yong; Xu, Baoliang; Yu, Jun
Abstract: Ixodes persulcatus is a species of hard tick which is a predominant tick species that spreads a wide array of serious human and animal pathogens. Here, we first assemble the complete mitogenome of I. persulcatus of China. The total length of the mitogenome was 14, 539 bp included 36 genes and with a mitogenome structure similar to other ticks. Phylogenetic tree was constructed based on the complete mitogenome of I. persulcatus and closely related 19 species ticks to assess their phylogenic relationship and evolution. We also analyze the differences between the mitogenomes of I. persulcatus of Japan and China. The complete mitogenome data would be useful for further study of I. persulcatus .